Fabrikasi Nanotubes Titanium Dioksida (TiO2) Menggunakan Metode Hidrotermal - Atik Setyani; Emas Agus Prastyo Wibowo (Syarif Hidayatullah State Islamic University, 2017)
Nanotubes received great attention because it has a high surface area. In this study, TiO2 nanotubes fabricated via hydrothermal method from synthesis of TiO2 nanoparticles via sol-gel method. Catalysts that have been synthesized later in the characterization by X-Ray Diffraction (XRD) to obtain the crystal size and crystallinity. Crystal size of TiO2 nanoparticles at a temperature of 450C is 13.78 nm. Then characterized by Transmission Electron Microscopy (TEM) to look at the formation of nanotubes. Characterization of TiO2 nanotubes with TEM shows that the structure of the tubes had already been formed TNTs although the growth has not been perfect. It can be seen from the structure TNTs who tend to be short and yet so irregular.DOI: http://dx.doi.org/10.15408/jkv.v0i0.5036